„Gravettians in the Altmühl Valley“? Comprehensive Reassessment and New Data from the Sequence from the Abri I im Dorf (Neuessing, Bavaria, Germany) - Calvo, Aitor; Pasda, Kerstin; Rutan, Nadja; Arrizabalaga, Alvaro; Uthmeier, Thorsten (Journal of Paleolithic Archaeology, 2024)
Due to the high density of cave and rock shelter sites, the Altmühl Valley is one of the most essential regions of southern German Palaeolithic research. The site presented in this paper, the Abri I im Dorf, lies within the main concentration of Palaeolithic sites found in this valley, extending along its lowest stretch between Riedenburg and its confluence into the Danube in Kelheim. We present the results achieved in reassessing the archaeo-stratigraphic sequence uncovered during the excavation campaign of 1959, including the first radiocarbon dating and comprehensive analysis of the lithic, faunal and bone industry evidence. Radiocarbon evidence points to occupations dated to ca. 27 ka cal BP. At the same time, the features of the lithic assemblage (blade industry with a predominance of burins and an important presence of backed tools) fit those of Late/Final Gravettian technocomplexes in the Danube region. However, the characteristic evidence traditionally associated with these industries (Kostënki knives and shouldered points) is scarce and highly questionable. The same applies to the “shovel-like” ivory object, typically related to the Pavlovian but with a doubtful determination as a shovel and no clear parallels in this and other industries of Gravettian tradition. The faunal remains revealed that hunting activities, which occurred between late summer and the beginning of winter, concentrated on reindeer. Nonetheless, new excavations and analyses are required to confirm all these preliminary results. In this sense, future work at the Abri I im Dorf can significantly contribute to our understanding of pre-LGM human settlement dynamics in the Upper Danub